The Gen Z Response to Islamic Mobile Banking Adoption: A Technology Acceptance Model with Cybersecurity Perspective - Mufidah, Diana; Nasrulloh, Nasrulloh (Jurnal Ilmu Ekonomi Terapan, 2025)
Objective: This study analyzes Generation Z’s behavioral response toward Islamic mobile banking adoption by extending the Technology Acceptance Model (TAM) with a cybersecurity perspective. The main research question addresses how perceived ease of use, perceived usefulness, and cybersecurity influence the adoption of Islamic digital financial technologies. This study is empirical and examines the interaction between user behavior and ethical dimensions in sharia-based digital financial services. Design/Methods/Approach: A quantitative approach was employed, utilizing primary data gathered from 100 respondents through an online survey. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) to examine the relationships among perceived ease of use (PEOU), perceived usefulness (PU), cybersecurity, and community response (CR). This method effectively identifies both direct and indirect effects among behavioral and trust-related variables within the TAM framework. Findings: The results show that PEOU and cybersecurity have a positive and significant effect on CR, while PU is insignificant. Both PEOU and PU positively affect cybersecurity, confirming the mediating roles of cybersecurity in shaping user trust and behavioral responses. This finding indicates that for Generation Z, usability and digital trust are more decisive than functional benefits alone. Originality/Value: This study contributes to digital finance literature by integrating cybersecurity into the TAM framework as a behavioral trust construct in Islamic financial systems. It provides new empirical evidence regarding young consumers’ responses to ethical and technological dimensions of Islamic digital banking. Practical/Policy implication: The findings emphasize the need for Islamic financial institutions to design mobile banking systems that are both user-friendly and secure. Enhancing transparency, interface simplicity, and cybersecurity literacy will strengthen user trust. Policymakers should develop cybersecurity standards aligned with Sharia principles to ensure ethical and inclusive digital transformation.